2021
DOI: 10.3389/fnut.2021.702659
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Disorders Promote Inflammation and Aggravate Spinal Cord Injury Through the TLR4/MyD88 Signaling Pathway

Abstract: Background: In spinal cord injury (SCI), systemic inflammation and the death of nerve cells in the spinal cord are life threatening. The connection between gut microbiota and signaling pathways has been a hot research topic in recent years. The Toll-like receptor 4/Myeloid differentiation factor 88 (TLR4/MyD88) signaling pathway is closely related to the inflammatory response. This study explored whether the gut microbiota imbalance could affect the TLR4/MyD88 signaling pathway to regulate SCI to provide a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Moreover, changes in gut microbiota composition following SCI could predict locomotor impairment (125). Additionally, gut microbiota dysbiosis can aggravate SCI by activating the TLR4/ Myeloid differentiation factor 88 signaling pathway (121).…”
Section: Spinal Cord Injury (Sci)mentioning
confidence: 99%
“…Moreover, changes in gut microbiota composition following SCI could predict locomotor impairment (125). Additionally, gut microbiota dysbiosis can aggravate SCI by activating the TLR4/ Myeloid differentiation factor 88 signaling pathway (121).…”
Section: Spinal Cord Injury (Sci)mentioning
confidence: 99%
“…Gut microbiota dysregulation can also deteriorate SCI by activating the TLR/MyD88 signaling pathway. 35 We also identified some pathways highly related to neuroprotection and axon regeneration. For instance, yes-associated protein (YAP) was upregulated in male C57BL/6 astrocytes and activated in a Hippo pathway-dependent manner post-SCI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, one function of the TLR4/MyD88 signaling pathway is promoting nerve cell death by inducing inflammation. Gut microbiota dysregulation can also deteriorate SCI by activating the TLR/MyD88 signaling pathway [ 35 ]. We also identified some pathways highly related to neuroprotection and axon regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study has found that modulating the microbiome can affect the expression of IL-1β, IL-6, and TNF-α ( 41 ). Transplantation of a disturbed gut microbiome exacerbates inflammatory damage, including stimulating the expression of pro-inflammatory factors IL-1β, IL-6, and TNF-α, and reducing the levels of anti-inflammatory IL-10, IL-4, and TGF-β ( 42 ). From this, we could speculate that the gut microbiome might affect epileptic seizures by regulating the expression of inflammatory factors while regulating M2 polarization.…”
Section: Discussionmentioning
confidence: 99%